2010
DOI: 10.1080/08927014.2010.482208
|View full text |Cite
|
Sign up to set email alerts
|

Drag force and surface roughness measurements on freshwater biofouled surfaces

Abstract: The detrimental effect of biofilms on skin friction for near wall flows is well known. The diatom genera Gomphonema and Tabellaria dominated the biofilm mat in the freshwater open channels of the Tarraleah Hydropower Scheme in Tasmania, Australia. A multi-faceted approach was adopted to investigate the drag penalty for biofouled 1.0 m x 0.6 m test plates which incorporated species identification, drag measurement in a recirculating water tunnel and surface characterisation using close-range photogrammetry. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The plates were then towed down the tank using the types of coatings under static and dynamic conditions. Andrewartha et al (2010) measured an increase of 99% in the drag coefficients of test plates due to biofilms in a recirculating water tunnel. Monty et al (2016) carried out experimental and numerical studies and predicted a 34% increase in total resistance of a very large crude oil carrier due to light calcareous tubeworm fouling.…”
Section: Experimental Facilities Model Details and Methodsmentioning
confidence: 99%
“…The plates were then towed down the tank using the types of coatings under static and dynamic conditions. Andrewartha et al (2010) measured an increase of 99% in the drag coefficients of test plates due to biofilms in a recirculating water tunnel. Monty et al (2016) carried out experimental and numerical studies and predicted a 34% increase in total resistance of a very large crude oil carrier due to light calcareous tubeworm fouling.…”
Section: Experimental Facilities Model Details and Methodsmentioning
confidence: 99%
“…Biofouling on the surfaces of heat exchangers, ships' hulls, pipelines, and other structures causes serious problems (Kerr et al 2003;Eguı´a et al 2008;Rao et al 2009;Andrewartha et al 2010). A thin layer of bacterial biofilm on the surfaces of heat exchangers significantly reduces heat transfer performance (Little and Lavoie 1979;Rao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gomphonema sp. have been reported from urban wetlands in India (Alakananda et al, 2013) and have been reported as the dominant biofouling diatom species on stainless steel surface biofilms after immersion in natural waters (Andrewartha et al, 2010). Recently, Yang et al (2015) while studying the seasonal variations in fouling diatom communities on the Yantai coast of China also reported Gomphonema sp.…”
Section: Discussionmentioning
confidence: 99%